Synthesis, Characterization and Electrochemical Sensing Property of W-MCM-41 - Thatshanamoorthy, V.; Narayanan, V. (Asian Journal of Chemistry, 2013)
Mesoporous tungsten incorporated MCM-41 (W-MCM-41) was prepared by direct hydrothermal method with different weight ratio of Si to W (Si/W = 25, 50, 100 and 150). The synthesized W-MCM-41 was characterized by low angle X-ray diffraction analysis, Fourier transform-infrared spectroscopy and UV-visible spectroscopy. From the XRD of W-MCM-41 it is observed that, when incorporation of tungsten into the MCM-41 matrix, the mesoporous structure is distorted slightly and hence the intensities are found to decrease with increase in tungesten concentration. The FT-IR spectrum of the samples showed that the tungesten was well incorporated within the MCM-41 framework. The morphological properties of the synthesized samples were characterized by scanning electron microscopy which showed that the synthesized samples comprise of highly agglomerated particles. The synthesized W-MCM-41 was used to modify glassy carbon electrode (W-MCM-41/GCE) and the modified electrode was used to detect 4-chlorophenol in a pH 7.4 phosphate buffer solution by cyclic voltammetry. At the W-MCM- 41/GCE, 4-chlorophenol oxidized at less positive potential with larger current response than the bare GCE. The proposed sensor exhibits great potential in the electrochemical sensing of 4-chlorophenol and related pollutants.